Improving ionospheric predictability requires accurate simulation of the mesospheric polar vortex - Harvey, V. Lynn; Randall, Cora E.; Bailey, Scott M.; Becker, Erich; Chau, Jorge L.; Cullens, Chihoko Y.; Goncharenko, Larisa P.; Gordley, Larry L.; Hindley, Neil P.; Lieberman, Ruth S.; Liu, Han-Li; Megner, Linda; et al. (Frontiers in Astronomy and Space Sciences, 2022)
The mesospheric polar vortex (MPV) plays a critical role in coupling the atmosphere-ionosphere system, so its accurate simulation is imperative for robust predictions of the thermosphere and ionosphere. While the stratospheric polar vortex is widely understood and characterized, the mesospheric polar vortex is much less well-known and observed, a short-coming that must be addressed to improve predictability of the ionosphere. The winter MPV facilitates top-down coupling via the communication of high energy particle precipitation effects from the thermosphere down to the stratosphere, though the details of this mechanism are poorly understood. Coupling from the bottom-up involves gravity waves (GWs), planetary waves (PWs), and tidal interactions that are distinctly different and important during weak vs. strong vortex states, and yet remain poorly understood as well. Moreover, generation and modulation of GWs by the large wind shears at the vortex edge contribute to the generation of traveling atmospheric disturbances and traveling ionospheric disturbances. Unfortunately, representation of the MPV is generally not accurate in state-of-the-art general circulation models, even when compared to the limited observational data available. Models substantially underestimate eastward momentum at the top of the MPV, which limits the ability to predict upward effects in the thermosphere. The zonal wind bias responsible for this missing momentum in models has been attributed to deficiencies in the treatment of GWs and to an inaccurate representation of the high-latitude dynamics. In the coming decade, simulations of the MPV must be improved.